RELATIONSHIP BETWEEN BASIC SANITATION AND DIARRHEA IN THE KAPASA COMMUNITY HEALTH CENTER - Yulia Delvira; Rahmawati Azis; Muhammad Rifai (Journal of Global Nutrition, 2022)
Basic sanitation is a basic effort to improve public health by providing a healthy environment and meeting health requirements including clean water facilities, availability of latrines, waste water disposal facilities (SPAL), and waste management facilities. The purpose of this study was to determine the relationship between basic sanitation and the incidence of diarrhea in the working area of the Kapasa Community Health Center. The type of research used is quantitative research using a Cross Sectional Study approach with a population of 60 people and sampling using the purposive sampling technique where the researcher relies on his own judgment when selecting the population to participate in the study, so that the sample obtained is 52 people. The variables studied are Clean Water Utilization, SPAL Management, and Waste Management. The results of this study based on statistical tests using the chi-square test found that there was no relationship between the use of clean water and the incidence of diarrhea (P value = 1.000 > = 0.05), there was a relationship between SPAL management and the incidence of diarrhea where (P value = 0.021 < 0.05), and there is a relationship between waste management and diarrhea incidence (P value=0.023 < = 0.05). The conclusion and suggestion from this research is that basic sanitation is still lacking in the working area of the Kapasa Community Health Center so that it is necessary to educate health workers to the community in order to maintain the environment so that the environment is clean and prevent diseases caused by the environment, especially diarrhea